2007
DOI: 10.1017/s095026880700903x
|View full text |Cite
|
Sign up to set email alerts
|

Arctic and Arctic-like rabies viruses: distribution, phylogeny and evolutionary history

Abstract: Forty-one newly sequenced isolates of Arctic and Arctic-like rabies viruses, were genetically compared to each other and to those available from GenBank. Four phylogenetic lineages of Arctic viruses were identified. Arctic-1 viruses circulate in Ontario, Arctic-2 viruses circulate in Siberia and Alaska, Arctic-3 viruses circulate circumpolarly, and a newly described lineage Arctic-4 circulates locally in Alaska. The oldest available isolates from Siberia (between 1950 and 1960) belong to the Arctic-2 and Arcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 25 publications
7
91
1
Order By: Relevance
“…2 (2006). These clusters were mainly in accordance with previously described phylogenetic groups (Mansfield et al, 2006;Kuzmin et al, 2008). At the amino acid level, the homology between the rabies virus isolates in this comparison was even greater; all except one isolate had 100% homology (data not shown).…”
Section: Pcr and Phylogenysupporting
confidence: 89%
See 2 more Smart Citations
“…2 (2006). These clusters were mainly in accordance with previously described phylogenetic groups (Mansfield et al, 2006;Kuzmin et al, 2008). At the amino acid level, the homology between the rabies virus isolates in this comparison was even greater; all except one isolate had 100% homology (data not shown).…”
Section: Pcr and Phylogenysupporting
confidence: 89%
“…For alignment and comparison, corresponding gene sequences from the nucleoprotein gene of previously reported (Mansfield et al, 2006;Johnson et al, 2007;Kuzmin et al, 2008) arctic rabies virus isolates were retrieved from GenBank (National Center for Biotechnology Information [NCBI]; Table 2). All sequences were aligned using two algorithms for comparison, namely Clustal V2 (Larkin et al, 2007) and Muscle 3.6 (Edgar, 2004).…”
Section: Polymerase Chain Reaction and Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…This tendency was also consistent for other groups outside the CosC, such as group IX (35,36). Dog rabies epizootics in the Americas seem to be characterized by the circulation of multiple geographic or temporal lineages that have either become extinct or merged over time (2,3,8,10,21,22,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 67%
“…Phylogenetic analyses revealed that Bhutanese RABV isolates were more closely related to the RABV strains from India and Arctic-like-1 viruses circulating in South Asia (Nadin-Davis et al, 2007;Kuzmin et al, 2008), and could be grouped together as a large cluster of the South Asian Arctic-like-1 viruses (Group I in Figure 2). Geographically, Bhutan lies in the same Himalayan region of the Indian subcontinent where the emergence and extensive circulation of the Arctic-like-1 rabies viruses has been confirmed in India (Nadin-Davis et al, 2007).…”
Section: Figurementioning
confidence: 99%